Catheter-associated urinary tract infection and biofilms: Dreaded duo in health settings - Ragani Chellaiyah Murugesan; Gowri Subbiah; Gracia Paul Lansingh; Poongodi Santhanakumarasamy (Journal of Current Research in Scientific Medicine)
Background: Urinary tract infections (UTIs) alone account for 30% of hospital infections, 80% of these are catheter-associated UTIs (CAUTI). Microbial film in indwelling medical devices worsens the existing medical condition and leads to multidrug resistance (MDR) and prolonged hospital stay. This cross-sectional study was done to find out the organisms causing CAUTI, their sensitivity pattern, the proportion of biofilm formation, and the sensitivity, specificity of different procedures in the demonstration of biofilm. Materials and Methods: Urine sample was collected from 307 patients with indwelling catheters. Direct Gram stain was performed from well-mixed uncentrifuged urine. Specimens were processed, organisms were isolated by standard microbiological procedures, and antimicrobial sensitivity testing was performed. Various methods such as Congo red agar, tube adherence, and microtiter plate methods were used to identify biofilm formation for all the isolates. Results: Out of 307 catheterized urine samples, a direct Gram stain was positive in 137 (44.62%) samples and culture positive in 148 (48.2%) samples. Out of 134 bacterial isolates, biofilm was observed by Congo red agar in 36 (27%), tube adherence in 59 (44%), and microtiter plate in 80 (60%) isolates. Escherichia coli (50.74%) was the predominant isolate followed by Klebsiella spp (26.11%). MDR was observed in 53 (66%) biofilm-forming isolates. Conclusions: Catheterized patients are prone to develop a microbial biofilm that is multidrug resistant and burdensome. Of the 80 biofilm-producing isolates, MDR was observed in 53 (66%). The effective ways to prevent CAUTI are strict adherence to indications for catheterization and, a bundle care approach with a preinsertion checklist.